Applications of Differential Subordination for Argument Estimates of Multivalent Analytic Functions. (26th February 2014) - Lu, Meng-Ting; Jia, Ting; Ling, Xing-Qian; Liu, Jin-Lin
Abstract : By using the method of differential subordinations, we derive some properties of multivalent analytic functions. All results presented here are sharp.